Proses Morfofonemik pada Bahasa Jawa Kabupaten Bengkalis - Aulia, Rifa; Baehaqie, Imam; Rustono, Rustono (GERAM: Gerakan Aktif Menulis, 2023)
This research discusses morphophonemic phenomena in the Javanese language in Bengkalis with a focus on sound changes that occur at the morpheme level. Morphophonemics, as a linguistic study that explores the relationship between morphemes (minimal meaning units) and phonemes (minimal sound units), is a theoretical basis for describing morphemic sound changes in Javanese. This study used a descriptive qualitative method. Research data was obtained from the results of Javanese speech by speakers. Research data was obtained from the results of data collection techniques using the listen, speak, note method. The data analysis technique is carried out through the following stages: 1) observing research data; 2) Transcription of research data; 3) Translating research data; 4) Classifying research data; 5) Analyzing changes in nasal meaning according to theory; 6) Draw conclusions from the research results. The research results show that the Javanese language on the island of Bengkalis experiences several morphophonemic phenomena, including changes in phonemes, addition of phonemes, and deletion of sounds at the morpheme level. If the prefix (N-) meets the phoneme /p/ it will change to /m/. Likewise with the prefixes (Sa-) and (Pa-), if they meet the initial phoneme of a vowel, the phoneme /a/ will disappear. Concrete examples are given to illustrate sound changes that occur in various morphemic contexts.